2015
DOI: 10.1007/s13320-015-0274-8
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent detection and identification in fiber-optical perimeter intrusion monitoring system based on the FBG sensor network

Abstract: Abstract:A real-time intelligent fiber-optic perimeter intrusion detection system (PIDS) based on the fiber Bragg grating (FBG) sensor network is presented in this paper. To distinguish the effects of different intrusion events, a novel real-time behavior impact classification method is proposed based on the essential statistical characteristics of signal's profile in the time domain. The features are extracted by the principal component analysis (PCA), which are then used to identify the event with a K-neares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results agree with the hypotheses of Wu et al 2015 andFriedli et al 2019 , who observed DAS response changing over time, suggesting that the coupling between the fiber optic cable and the host medium may change due to aging and seasonal environmental changes. For impact source locations offset from the fiber optic cable array, the impactgenerated seismic wave would travel from the ground surface of the undisturbed native silty sand material towards the trench material containing the fiber optic cable.…”
Section: Soil Moisture and Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with the hypotheses of Wu et al 2015 andFriedli et al 2019 , who observed DAS response changing over time, suggesting that the coupling between the fiber optic cable and the host medium may change due to aging and seasonal environmental changes. For impact source locations offset from the fiber optic cable array, the impactgenerated seismic wave would travel from the ground surface of the undisturbed native silty sand material towards the trench material containing the fiber optic cable.…”
Section: Soil Moisture and Temperaturesupporting
confidence: 92%
“…Vibrations induced by activity near the installed DAS induce submicroscopic changes in the fiber length, core refractive index, and core diameters (Liu et al 2016). DAS can be trained to identify an activity of interest (Madsen et al 2008, Wu et al 2015, and Friedli et al 2019…”
Section: Geotechnical Subsurface Investigationsmentioning
confidence: 99%
“…In the experiment, the average recognition rate of five sample signals was as high as 96.67%, achieving a very high accuracy. 20) It can be seen that the use of machine learning related algorithms in data processing of optical fiber sensor systems would be far superior to traditional computational methods, greatly improving the convenience and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of intrusion signals has been a topic of interest among researchers in perimeter security. Wu et al applied principal component analysis to extract features and identify events using a k-nearest neighbor classifier [7]. However, the limited dataset used in their study may limit the generalizability of their approach, making it potentially unsuitable for substation perimeter intrusion systems.…”
Section: Introductionmentioning
confidence: 99%